Analysis of Human Immune Response against Salivary Glands Protein Extract of Anopheles sundaicus. L in Malaria Endemic Area (Indonesian Society for microbiology, 2017)
Malaria is an infectious disease caused by Plasmodium, which is transmitted by Anopheles mosquitoes as vectors. Malaria transmission begins when an infected mosquito takes blood meal from healthy human. Mosquitoes will release parasite and components of saliva into the host's body. Saliva contains components (proteins) that affect the host's hemostasis and immune respose, such as vasomodulator and immunomodulators. Imunomudulator could act as immunosuppressive factors that can suppress nonspecific immune system of the host and modulate the change of T helper 1 (Th1) toward T helper 2 (Th2) response, which is advantageous for malaria parasite to infect human host. This research wanted to evaluate human immune respons in endemic area against salivary gland protein extract (SGPE) from its major malaria vector i.e. Anopheles sundaicus (An. sundaicus). Analysis of human immune response was conducted quantitatively by ELISA (Enzyme Link Immunosorbend Assay) towards IgG from human sera samples after cross reacted with SGPE. The results showed that exposures to An. sundaicus were able to induce high levels of IgG. IgG anti salivary proteins of An. sundaicus is higher than the levels of IgG anti salivary proteins of Ae. aegypti. Furthermore, the age group 11-40 years with the highest bites probability, had the highest IgG levels compared to other age groups.